DNA studies using atomic force microscopy: capabilities for measurement of short DNA fragments - Pang, Dalong; Thierry, Alain R.; Dritschilo, Anatoly (Frontiers in Molecular Biosciences, 2015)
Short DNA fragments, resulting from ionizing radiation induced DNA double strand breaks (DSBs), or released from cells as a result of physiological processes and circulating in the blood stream, may play important roles in cellular function and potentially in disease diagnosis and early intervention. The size distribution of DNA fragments contribute to knowledge of underlining biological processes. Traditional techniques used in radiation biology for DNA fragment size measurements lack the resolution to quantify short DNA fragments. For the measurement of cell-free circulating DNA (ccfDNA), real time quantitative Polymerase Chain Reaction (q-PCR) provides quantification of DNA fragment sizes, concentration and specific gene mutation. A complementary approach, the imaging-based technique using Atomic Force Microscopy (AFM) provides direct visualization and measurement of individual DNA fragments. In this review, we summarize and discuss the application of AFM-based measurements of DNA fragment sizes. Imaging of broken plasmid DNA, as a result of exposure to ionizing radiation, as well as ccfDNA in clinical specimens offer an innovative approach for studies of short DNA fragments and their biological functions.